IDENTIFYING LANGUAGE PROFICIENCY AND SLA OF ENGLISH EDUCATION DEPARTMENT STUDENTS FOR DESIGNING AN INTERCULTURAL COMMUNICATION E-BOOK - Ficayuma, Lina Aris (International Research-Based Education Journal, 2022)
Identifying the student’s needs and proficiency in a language is a pivotal factor before designing the syllabus and developing an intercultural communication e-book, which led the researcher to conduct this study. 27 students English education department is selected as representative research subjects. This research is part of R&D in the first part specifically, identifying and exploring the needs. Data collection for this study was obtained through a TEP test, document analysis of speaking class, and structured interviews. The data collection was analyzed quantitively and qualitatively using 6 steps: collection, reduction, display, conclusion drawing, and verification. As a result, almost half of students, specifically 44% of students obtain an average score of 546 to 600 or C level, while 52% of students obtain an average score of 450 to 546 out of 677 or in B level based on CEFR standard global scale. In addition, 51.85% of students pass academic speaking, 25.92 % of students pass critical speaking, and 22.23% of students pass basic speaking. In addition, the students pass with an average score of A or A- grade. Then English as a second foreign language is acquired after the Arabic language. In short, IC e-book design should be considering the feasibility of languages such as students' language development, communication, unity, cohesion, and coherence aspects.